Dimers or Solid‐State Solvation? Intermolecular Effects of Multiple Donor–Acceptor Thermally Activated Delayed Fluorescence Emitter Determining Organic Light‐Emitting Diode Performance. Issue 14 (3rd March 2021) - Imbrasas, Paulius; Lygaitis, Ramūnas; Kleine, Paul; Scholz, Reinhard; Hänisch, Christian; Buchholtz, Stephanie; Ortstein, Katrin; Talnack, Felix; Mannsfeld, Stefan C. B.; Lenk, Simone; Reineke, Sebastian
Abstract: Organic light‐emitting materials exhibiting thermally activated delayed fluorescence (TADF) show great promise for improving display applications. Recently, intermolecular effects between emitting molecules have been given more attention, revealing strong solid‐state solvation or aggregation induced changes of sample performance. Implications of this on device performance are not yet fully covered. In this work, a thorough investigation of a novel TADF emitter, methyl 2, 3, 4, 5, 6‐penta(carbazol‐9‐yl)benzoate (5CzCO2Me), is provided. Steady‐state emission spectra reveal a luminescence redshift with increasing emitter concentration in a small molecule host. In all investigated concentrations, the emission profile remains the same; thus, the redshift is attributed to the solid‐state solvation effect. The highest photoluminescence quantum yield (PLQY) is achieved in the 20 wt% sample, reaching 66%. The best organic light‐emitting diode (OLED) in terms of current–voltage–luminance and external quantum efficiency (EQE) parameters is the device with 60 wt% emitter concentration, reaching maximal EQE values of 7.5%. It is shown that the emitter transports holes and that charge‐carrier recombination does not take place on the bandgap of the host, but rather, a mixed host–guest concentration‐dependent recombination is seen. The hole‐transporting properties of 5CzCO2Me allow for a new dimension in tuning the device performance by controlling the emitter concentration. Abstract : A thorough investigation of a thermally activated delayed fluorescence (TADF) emitter, methyl 2, 3, 4, 5, 6‐penta(carbazol‐9‐yl)benzoate (5CzCO2Me), is provided, attributing the intermolecular effects to solid‐state solvation effect (SSSE) and excluding dimer formation. Emitter concentration becomes an important parameter for organic light‐emitting diode (OLED) optimization. The emitter is responsible for light emission and charge‐carrier transport, leading to a novel pathway for device improvements.